Karangsari Berdaya:Peningkatan Ekonomi Masyarakat melalui Optimalisasi Potensi Desa Berbasis GIS - Vina Nurul Husna; Vitradesie Noekent; Nina Witasari (Jurnal Dharma Indonesia, 2026)
Based on the analysis of the target community, there are three partner problems. First, it is unlikely that a village with conditions like Karangsari's experiences extreme poverty. If the tourism sector develops well, there is little chance that nearby villages will not also benefit from the economic boost. Secondly, in the south of Karangsari village, there is the Jlantah Dam, which serves to irrigate rice fields and community gardens, so the possibility of water shortages to develop agriculture should decrease. Third, from the cultural sector, Karangsari, part of Karanganyar, is referred to as 'the heart of the archipelago' due to the glory of the Hindu-Buddhist kingdom in the past, and it should also contribute to improving Karangsari village's economy. The solution offered consists of three planned activities.  First, socializing with the village community about the potential of Karangsari village and the activities that support it. Second, providing training to community groups to optimize village potential, containing several programs to support the development of village potential and economic improvement. Third, digitizing village potential and development makes it easier for relevant stakeholders to develop the village and determine policies to be applied in Karangsari village. Digitalization of village potential in the form of a webGIS that contains information on village potential across various sectors, in addition to information on the actual development of village utilization.